Authentication Technologies for Cloud Computing, IoT and Big Data - Alginahi, Yasser M; Nomani Kabir, Muhammad (The Institution of Engineering and Technology, 2019)
Critical systems and infrastructure rely heavily on ICT systems and networks where security issues are a major concern. Authentication methods verify that messages come from trusted sources and guarantee the smooth flow of information and data. In this edited reference, the authors present state-of-art research and development in authentication technologies including challenges and applications for Cloud Technologies, IoT and Big Data. Topics covered include authentication; cryptographic algorithms; digital watermarking; biometric authentication; block ciphers with applications in IoT; identification schemes for Cloud and IoT; authentication issues for Cloud applications; cryptography engines for Cloud based on FPGA; and data protection laws.